Exploring the interface between biomedical sciences and the arts through the global sci/art network MEDinART (Journal of EAHIL, 2019)
MEDinART (www.MEDinART.eu) is a continuously growing global sci/art network that connects biomedical sciences with technology and arts through the work of more than 170 artists from 30 countries who are influenced by aspects of biomedical sciences. MEDinART aims are to unite the artists who are influenced by biomedicine, to connect different countries and cultures through the universal language of sci/art, and to globalise the biomedical-inspired art movement. Inspired and created by the Author, Vasia Hatzi, MEDinART explores the interface between biomedicine with arts through talks, exhibitions and articles in events, conferences and journals around the world. Here we present the goals of MEDinARÎ¤, its philosophy and the messages that it delivers to society through its activities.